A new species of Idona DeLong (Hemiptera: Cicadellidae: Typhlocybinae) from Mexico, with an annotated list of species - Pinedo-Escatel, J.a.; Blanco-Rodríguez, E. (Zootaxa, 2016)
A new dikraneurine leafhopper, Idona dmitrievi sp. nov., is described and illustrated from Mexico. An annotated checklist and a key for Mexican species are also provided.